Local injury to the endometrium does not improve the implantation rate in good responder patients undergoing in-vitro fertilization - Leili Safdarian; Shohre Movahedi; Ashraf Aleyasine; Marzie Aghahosaini (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2011)
Background: Despite numerous developments in the field of assisted reproduction the implantation rate remains low .Recent studies suggested that local injury to endometrium in controlled ovarian hyper stimulation cycle improves implantation rate. Studies have attempted to intervene in the development of endometrium.Objective: The aim of the present study was the exploration of the possibility that local injury of the endometrium increases implantation rate.Materials and Methods: In this interventional study, 100 good responders to hormone stimulation patients were divided into control group (n=50) and experimental group (n=50) which undergo endometrial biopsy by biopsy catheter )piplle) on day 21 of their previous menstrual cycle with use of contraceptive pills before the IVF-ET treatment. In total, 26 patients were removed from the study because the number of stimulated follicles were below 3, or there was no embryo or there was the risk of OHSS. The remaining patients were 33 in experimental group and 41 in the control group.Results: There were no significant differences between the two groups in terms of the age of the patients, duration of infertility and BMI, base line FSH level and responses to hormone stimulation. The rates of embryo implantation, chemical and clinical pregnancy in the experimental group were 4.9%, 18.2% and 12.1% with no significant differences with the control group (6.7%, 19.5%, 17.1%). Cancellation rate was 26%.Conclusion: In our study, endometrial biopsy didn't increase the chances to conceive at the following cycle of treatment.